Predicting the Effect of Sterilization Policy on the Reserved Money in the Iraqi Economy until 2030 Using ARIMA and ANN Models: Predicting the Effect of Sterilization Policy on the Reserved Money in the Iraqi Economy until 2030 Using ARIMA and ANN Models - Neamah, Sameer; Yousif, Akram (Humanities Journal of University of Zakho, 2022)
Abstract The Central Bank’s borrowing of a portion of excess liquidity and its accumulation in its balance sheet as liabilities with interest, its frequent raising of the legal reserve ratios, intervening in the exchange market through the purchase of foreign currency, then absorbing the effect of this purchase on local liquidity, providing deposit facilities with interest and offering its Central Bank orders to banks in the subsidiary market all come under the title of sterilization policies. This is quite evident from minimizing local crediting. In an attempt to control excess liquidity, the factors determining monetary sterilization policy and reserved money have been attended to so as to concisely forecast the course of the monetary variables until the year 2030 in order to maintain the stability of the monetary basis from the impact of the changes in oil price. This has been conducted through the adoption of prediction models of autoregression moving averages (ARIMA) model in addition to the artificial neural networks model (ANN) since the growth in government expenditure indicates that the monetization of oil revenues has caused a structural fiscal deficit in the Iraqi economy. Such a deficit should be restricted by the sterilization policy through monetary policy tools. Based on this, the balance of the budget in an economy depending on oil revenue cannot guarantee economic stability unless public spending is managed with a degree of independence from the fluctuations in oil price.